Awareness of Breast Cancer and its Early Detection Measures among Female Students, Northern Ethiopia - Tesfay Hailu; Hailemariam Berhe; Desta Hailu (Intelektual Pustaka Media Utama, 2016)
Globally breast cancer is the most common of all cancers. Since risk reduction strategies cannot eliminate the majority of breast cancers, early detection remains the cornerstone of breast cancer control. This paper, therefore, attempts to assess the awareness of breast cancer and its early detection measures among female students in Mekelle University, Ethiopia. An institution based cross-sectional study was conducted on randomly selected female students. Multistage sampling technique was employed to select the participants. A pre-tested structured questionnaire was used. Data analysis was carried out using SPSS version 16. In this study, 760 students participated making a response rate of 96 percent. Respondents with good knowledge score for risk factors, early detections measures and warning signs of breast cancer were 1.4 percent, 3.6 percent and 22.1 percent respectively. The majority 477 (62.8 percent) of participants practiced self-breast examination. In conclusion the participants had poor knowledge of risk factors, early detection measures and early warning signs of breast cancer.Therefore, the Ministry of health of Ethiopia together with its stalk holders should strengthen providing IEC targeting women to increase their awareness about breast cancer and its early detection measure.